1978
DOI: 10.1203/00006450-197803000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency in the Rat: Biochemical Studies of Brain Metabolism

Abstract: SummaryMitochondria were prepared from liver as described previStudies were performed to determine the effects of iron deficiency on brain metabolism in rats. Concentrations of cytochrome pigments, oxidative phosphorylation, and catalase and monoamine oxidase activities in brain tissue were unaffected by iron deficiency. However, activities of aldehyde oxidase, a key enzyme in the pathway of serotonin degradation, were significantlv reduced. and concentrations of serotonin and total 5-hydroxyindole compounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 6 publications
4
36
0
Order By: Relevance
“…Furthermore, as occurs in humans suffering from severe anaemia, there was an increase in the number of leucocytes and platelets, and also in the concentration of cortisol in serum. An explanation for the latter consequence may be deduced from the results of Youdim et al (1980), who found a reduction in the activity of monoaminooxidase (MAO) in iron-deficient rats, and of Mackler et al (1978), who reported a low level of aldehyde oxidase activity. These enzymatic changes produce an increase in the endogenous levels of circulating catecholamines, which are known to increase the release rate of adrenocorticotrophic hormone, which in turn produces an increase in the production of glucocorticoids Campos et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as occurs in humans suffering from severe anaemia, there was an increase in the number of leucocytes and platelets, and also in the concentration of cortisol in serum. An explanation for the latter consequence may be deduced from the results of Youdim et al (1980), who found a reduction in the activity of monoaminooxidase (MAO) in iron-deficient rats, and of Mackler et al (1978), who reported a low level of aldehyde oxidase activity. These enzymatic changes produce an increase in the endogenous levels of circulating catecholamines, which are known to increase the release rate of adrenocorticotrophic hormone, which in turn produces an increase in the production of glucocorticoids Campos et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the jitteriness-positive patients also had lower MCV and MCH, and this may indicate a relative hypoxic state which may intensify the acute adrenergic effects of TCA. Iron deficiency produces an increase in serotonin and its metabolites [8] and jitteriness may also be related to altered serotonin function. It is interesting to note that fluoxetine, a relatively selective serotonin up take blocker also produces jitteriness, restlessness, agita tion and insomnia in panic disorder patients [9], The importance of these findings is that the above indices may help to identify those panic disorder patients who are at a higher risk to develop jitteriness.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models, using rats, have been employed and biochemical studies of changes in heart (Blayney et al, 1976), brain (Mackler et al, 1978) and striated muscle (Finch et al, 1976) reported. However, little information is available on the oral mucosa, which usually shows marked atrophy under such conditions.…”
Section: Discussionmentioning
confidence: 99%